2021
DOI: 10.1093/infdis/jiab545
|View full text |Cite
|
Sign up to set email alerts
|

Urban Particulate Matter Impairment of Airway Surface Liquid–Mediated Coronavirus Inactivation

Abstract: Air pollution particulate matter (PM) is associated with SARS-CoV-2 infection and severity, although mechanistic studies are lacking. We tested whether airway surface liquid (ASL) from primary human airway epithelial cells is antiviral against SARS-CoV-2 and 229E-CoV (responsible for common colds), and whether PM (urban, indoor (IAP), volcanic ash) affected ASL antiviral activity. ASL inactivated SARS-CoV-2 and 229E-CoV. Independently, urban PM also decreased SARS-CoV-2 and 229E-CoV-2 infection, and IAP decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…It has been proposed that vitamin D deficiency increases the risk of COVID-19 incidence and severity [ 40 ]. We recapitulated our previous work demonstrating ASL to be virucidal [ 41 ], however, we found no difference in ASL-mediated 229E-CoV viral inactivation between calcitriol-treated and untreated hAEC ASL. This is consistent with a recent finding from the United Kingdom where blood 25(OH)D concentrations did not correlate with COVID-19 infection risk [ 42 ].…”
Section: Discussionsupporting
confidence: 87%
“…It has been proposed that vitamin D deficiency increases the risk of COVID-19 incidence and severity [ 40 ]. We recapitulated our previous work demonstrating ASL to be virucidal [ 41 ], however, we found no difference in ASL-mediated 229E-CoV viral inactivation between calcitriol-treated and untreated hAEC ASL. This is consistent with a recent finding from the United Kingdom where blood 25(OH)D concentrations did not correlate with COVID-19 infection risk [ 42 ].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, since many of the genes assayed in this study are involved in general antiviral host defense, these results may translate to other viral pathogens of public health importance. Recently, urban PM was shown to impair antiviral properties of airway epithelial cultures toward SARS-CoV-2 and 229E-CoV, which causes the common cold ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…As recently discussed (Woodby et al, 2021), virus incubation with urban PM decreased infectivity for enveloped bacteriophage Φ6 but enhanced infection by nonenveloped Φ174, possibly due to PM damage of lipid membranes in enveloped viruses (Groulx et al, 2018). In a recent mechanistic study, Stapleton et al (2022) demonstrated that urban PM affects SARS-CoV-2 and human common cold alphacoronavirus 229E (CoV-229E) infectivity by decreasing viral viability while impairing viral inactivation by primary human epithelial cells airway surface liquid (ASL). The results showed for the first time that urban PM consistently inactivated both coronaviruses in vitro, thereby decreasing ambient viral titers before inhalation (Stapleton et al, 2022).…”
Section: Resultsmentioning
confidence: 91%
“…In a recent mechanistic study, Stapleton et al (2022) demonstrated that urban PM affects SARS-CoV-2 and human common cold alphacoronavirus 229E (CoV-229E) infectivity by decreasing viral viability while impairing viral inactivation by primary human epithelial cells airway surface liquid (ASL). The results showed for the first time that urban PM consistently inactivated both coronaviruses in vitro, thereby decreasing ambient viral titers before inhalation (Stapleton et al, 2022).…”
Section: Resultsmentioning
confidence: 99%